Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1021/acscombsci.8b00014
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Modification of Tryptophan-Containing Peptides

Abstract: We herein present a broadly useful method for the chemoselective modification of a wide range of tryptophan-containing peptides. Exposing a tryptophan-containing peptide to 2,3-dichloro-5,6-dicyano-1,4-benzoquinone (DDQ) resulted in a selective cyclodehydration between the peptide backbone and the indole side chain of tryptophan to form a fully conjugated indolyl-oxazole moiety. The modified peptides show a characteristic and significant emission maximum at 425 nm, thus making the method a useful strategy for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 34 publications
(23 reference statements)
0
10
0
Order By: Relevance
“…Additionally, the yields dropped slightly to 56-78 % when employing other kinds of manganese (Table 1, entries 8-10). The reaction failed to proceed using other transition metals such as copper, cobalt, nickel, and palladium, highlighting that manganese electrocatalysis is required for this approach (Table S1, entries [13][14][15][16]. Optimization revealed that NaN 3 was the best azide source compared to the other azide reagents tested (Table S1, entries [17][18][19][20].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the yields dropped slightly to 56-78 % when employing other kinds of manganese (Table 1, entries 8-10). The reaction failed to proceed using other transition metals such as copper, cobalt, nickel, and palladium, highlighting that manganese electrocatalysis is required for this approach (Table S1, entries [13][14][15][16]. Optimization revealed that NaN 3 was the best azide source compared to the other azide reagents tested (Table S1, entries [17][18][19][20].…”
Section: Resultsmentioning
confidence: 99%
“…Scientists anticipate the potential value of strategies to modify other sites that could be exploited for further late‐stage peptide modification. The aromatic tryptophan (Trp) side chain plays an essential role in peptides and proteins, and as such has become an attractive target for late‐stage modification [6–13] . Furthermore, the Trp side chain is an important precursor for the synthesis of fascinating indoline scaffolds with intriguing biological properties by dearomatization [14]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[32] A notable example of a synthetic route resembling the net reaction presented here is the selective introduction of indolyloxazole moieties into Trp sites of peptides by treatment with 2,3-dichloro-5,6-dicyano-1,4-benzoquinone (DDQ), but the mechanism has not been examined. [37] We concluded this study by evaluating the synthetic potential of IoxAB in precursor-directed biosynthetic experiments. Supplementing P. entomophila cultures with 23 carboxylic acid test substrates, 6 compounds yielded the expected molecular ions in HRMS analyses for the corresponding indolyloxazole and N-acyl precursor (Supporting Information, Table S6).…”
Section: Angewandte Chemiementioning
confidence: 96%
“…Mechanisms involving radical addition to the carbonyl oxygens of esters or amides were discussed in several synthetic transformations [35, 36] and suggested by DFT calculations as energetically feasible [32] . A notable example of a synthetic route resembling the net reaction presented here is the selective introduction of indolyloxazole moieties into Trp sites of peptides by treatment with 2,3‐dichloro‐5,6‐dicyano‐1,4‐benzoquinone (DDQ), but the mechanism has not been examined [37] …”
Section: Figurementioning
confidence: 99%